Eksistensialisme dan Pendidikan Islam - Voullin Hamzah; Herwina Bahar (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Philosophy emerges from a crisis, where this crisis makes someone try to find the truth. Thus philosophy is a journey from one crisis to another. In existential philosophy, humans are considered as subjects. Because human reality today is influenced by various crises and is surrounded by various problems, the human form studied by existentialism is not the form that we rationalize, but the form that exists. This research aims to explain the flow of existentialism in Islamic educational philosophy. Qualitative methods were used in this research. Based on the results of research and discussion, it can be concluded that existentialism is a philosophy which believes that all phenomena arise from existence. In general, existence means existence. Existence specifically is the way humans exist in the world. The way humans live in the world is different from the way things live. The object is not aware of its existence. People make everything more meaningful. To differentiate between these two ways of existence, the philosophy of existentialism states that objects "exist" while humans "exist". By understanding their existence, humans will be able to know their God well and make them the best human beings.